Chiral Plasmonic Hybrid Nanostructures: A Gateway to Advanced Chiroptical Materials - Tan, Lili; Fu, Wenlong; Gao, Qi; Wang, Peng‐peng (Advanced materials (Weinheim), 2024)
Chirality introduces a new dimension of functionality to materials, unlocking new possibilities across various fields. When integrated with plasmonic hybrid nanostructures, this attribute synergizes with plasmonic and other functionalities, resulting in unprecedented chiroptical materials that push the boundaries of the system's capabilities. Recent advancements have illuminated the remarkable chiral light–matter interactions within chiral plasmonic hybrid nanomaterials, allowing for the harnessing of their tunable optical activity and hybrid components. These advancements have led to applications in areas such as chiral sensing, catalysis, and spin optics. Despite these promising developments, there remains a need for a comprehensive synthesis of the current state‐of‐the‐art knowledge, as well as a thorough understanding of the construction techniques and practical applications in this field. This review begins with an exploration of the origins of plasmonic chirality and an overview of the latest advancements in the synthesis of chiral plasmonic hybrid nanostructures. Furthermore, representative emerging categories of hybrid nanomaterials are classified and summarized, elucidating their versatile applications. Finally, the review engages with the fundamental challenges associated with chiral plasmonic hybrid nanostructures and offer insights into the future prospects of this advanced field. Emerging chiral plasmonic hybrid nanostructures that integrate chirality, plamonics, and rich functionalities into single entities are introduced in this review. A comprehensive overview of recent advancements is provided, including the origins of chirality, rationale design and construction techniques, and versatile applications. Additionally, current challenges and future prospects in this field are discussed in detail.